FolVps9, a Guanine Nucleotide Exchange Factor for FolVps21, Is Essential for Fungal Development and Pathogenicity in Fusarium oxysporum f. sp. lycopersici - Li, Bing; Mao, Hui-Ying; Zhang, Zhao-Yang; Chen, Xi-Jun; Ouyang, Shou-Qiang (Frontiers in Microbiology, 2019)
The soil-borne, asexual fungus Fusarium oxysporum f.sp. lycopersici (Fol) is the causal agent of tomato wilt disease. Autophagy plays a crucial role in the development and virulence of Fol. The Fol endosomal system is highly dynamic and has been shown to be associated with conidiogenesis and pathogenicity. Rab GTPases and the regulators are highly conserved in regulating autophagy and endocytosis in most eukaryotes. Identification and characterization of additional Rab regulators in fungal pathogens should facilitate the understanding of the autophagy and endocytosis in different filamentous fungi. Here, we have identified and characterized the yeast VPS9 homolog FolVPS9 in Fol. Targeted gene deletion showed that FolVPS9 is important for growth, conidiation and virulence in Fol. Cytological examination revealed that FolVps9 co-localized with FolVps21 (a marker of early endosome) and played a critical role in endocytosis and autophagosome degradation. Pull-down assays showed that FolVps9 interacted with FolVps21, which was also important for development and plant infection in Fol. Yeast two-hybrid, bimolecular fluorescence complementation and co-immunoprecipitation assays revealed that FolVps9 specifically interacts with the GDP-bound form of FolVps21. Furthermore, a constitutively active form of FolVps21 (Q72L) was able to rescue defects of ΔFolvps9 and ΔFolvps21 mutants. In summary, our study provides solid evidence that FolVps9 acts as a FolVps21 guanine nucleotide exchange factor (GEFs) to modulate endocytosis and autophagy, thereby controlling vegetative growth, asexual development and pathogenicity in Fol.